Enerji sistemlerində rele mühafizəsi və avtomatikanın İşlənməsi - Talıbov, Əlihüseyin; Əfəndiyev, Tahir; Orucov, Əli; Əlizadə, Əliağa (My University, 2024)
In the dissertation, potential power deficits in energy systems were investigated, and the issue of normalization in power-generating units was examined. Methods for resolving power shortage problems in energy systems were analyzed, focusing on the technology for connecting automatic frequency load shedding (AFLS) stages and reserve energy sources to the network. After addressing the power deficit, the issue of automatic frequency reconnection was analyzed. Particular attention was paid to preventing erroneous disconnections due to short-term frequency drops. Operational current protection was specified for the activation of relay protection, automation devices, and control and inspection equipment.
Relay Protection and Automation in Power Systems
Keywords: Alçaldıcı transformator; Simmetrik qısaqapanma cərəyanları; Step-down transformer; Symmetrical short-circuit currents